Factors determine of students attitude toward PTPTN educational loan repayment / Mohamed Shafeeq Abd Wahap and Qurratu’ain Abu Kashim - Abd Wahap, Mohamed Shafeeq; Abu Kashim, Qurratu’ain (Faculty of Business and Management, 2013)
All this time, many researchers have conducted the study about determinants of student’s attitude towards PTPTN educational loan repayment. This research has conducted to find whether the four independent variables, which is knowledge, media awareness, parental influence and perception. About 100 respondents answer the questionnaires by using snow ball method. By using the Statistical Package for the Social Science (SPSS), all the data gathered were analyzed.Through this study, the result was found from the reliability, frequency, Pearson correlation, multiple regressions. Thus, our findings have one independent variable significant relationship towards students’ attitude towards PTPTN educational loan repayment.